The Impact of Daubert on the Admissibility of Forensic Anthropology Expert Testimony. Issue 3 (26th February 2015) - Lesciotto, Kate M.
Abstract Forensic anthropologists anticipated a significant impact from the 1993 Supreme Court Daubert decision, which addressed the standard of admissibility for expert testimony. In response, many forensic articles cited Daubert in the search for objective techniques or a critique of established subjective methods. This study examines challenges to forensic anthropological expert testimony to evaluate whether Daubert has actually affected the admissibility of such testimony. Thirty cases were identified that addressed the admissibility of the testimony, including 14 cases prior to Daubert and 16 after Daubert. Examination of these cases indicates that post‐Daubert cases do not result in more exclusions. Yet, this lack of exclusions may instead be viewed as a manifestation of the field's overall surge toward more objective and quantifiable techniques in a self‐regulating response to Daubert.